Cucurbitacin IIa Ameliorates DSS-Induced Ulcerative Colitis via Enhancing Intestinal Barrier Function and Inhibiting PERK/ATF4/CHOP Signaling Pathway - Yang, Yang; Yang, Qiong (Turkish Journal of Gastroenterology, 2024)
Background/Aims: The primary intent of this manuscript is to ascertain the effect of cucurbitacin IIa on ulcerative colitis (UC) and illus trate the potential mechanisms based on intestinal barrier function and the PERK/ATF4/CHOP signaling pathway. Materials and Methods: The UC mouse model was constructed by drinking 3% dextran sulfate sodium (DSS) for 1 week. The colonic tissues were stained with HE to assess pathological changes. The enzyme linked immunosorbent assay was used to measure myelo peroxidase (MPO) activity and levels of IL-1β, IL-6, and TNF-α. The western blot and immunohistochemistry methods were performed to analyze the expressions of PERK/ATF4/CHOP pathway-associated proteins. The quantitative real-time polymerase chain reaction (qRT-PCR) and immunofluorescence analysis were carried out to determine the expressions of ZO-1, claudin-1, occludin mRNA, and protein. Results: In comparison with the model group, cucurbitacin IIa obviously increased body weight and colon length, reduced disease activity index value and MPO activity, and ameliorated the degree of histopathological damage. Inflammatory factor levels were considerably reduced in the cucurbitacin IIa-intervention groups compared to the model group. The western blot and immunohistochemistry results indicated that, compared with the model group, cucurbitacin IIa significantly abolished the protein expressions of p-PERK, p-eIF2α, ATF4, and CHOP. The results of qRT-PCR and immunofluorescence revealed that cucurbitacin IIa greatly elevated the expressions of ZO-1, claudin-1, occludin mRNA and protein. Conclusion: Cucurbitacin IIa dramatically ameliorates DSS-induced UC symptoms via suppressing the PERK/ATF4/CHOP pathway and reinforcing enteric barrier function. Cite this article as: Yang Y, Yang Q. Cucurbitacin IIa ameliorates DSS-induced ulcerative colitis via enhancing intestinal barrierfunction and inhibiting PERK/ATF4/CHOP signaling pathway. Turk J Gastroenterol. 2025;36(4):229-240.